Higher rates of triple‐class virological failure in perinatally HIV‐infected teenagers compared with heterosexually infected young adults in Europe. Issue 3 (14th September 2016) - Judd, A; Lodwick, R; Noguera‐Julian, A; Gibb, DM; Butler, K; Costagliola, D; Sabin, C; van Sighem, A; Ledergerber, B; Torti, C; Mocroft, A; Podzamczer, D; et al.
Abstract : Objectives: The aim of the study was to determine the time to, and risk factors for, triple‐class virological failure (TCVF) across age groups for children and adolescents with perinatally acquired HIV infection and older adolescents and adults with heterosexually acquired HIV infection. Methods: We analysed individual patient data from cohorts in the Collaboration of Observational HIV Epidemiological Research Europe (COHERE). A total of 5972 participants starting antiretroviral therapy (ART) from 1998, aged < 20 years at the start of ART for those with perinatal infection and 15–29 years for those with heterosexual infection, with ART containing at least two nucleoside reverse transcriptase inhibitors (NRTIs) and a nonnucleoside reverse transcriptase inhibitor (NNRTI) or a boosted protease inhibitor (bPI), were followed from ART initiation until the most recent viral load (VL) measurement. Virological failure of a drug was defined as VL > 500 HIV‐1 RNA copies/mL despite ≥ 4 months of use. TCVF was defined as cumulative failure of two NRTIs, an NNRTI and a bPI. Results: The median number of weeks between diagnosis and the start of ART was higher in participants with perinatal HIV infection compared with participants with heterosexually acquired HIV infection overall [17 (interquartile range (IQR) 4–111) vs . 8 (IQR 2–38) weeks, respectively], and highest in perinatally infected participants aged 10–14 years [49 (IQR 9–267) weeks]. The cumulative proportion with TCVF 5 years after starting ART was 9.6% [95% confidence interval (CI) 7.0−12.3%] in participants with perinatally acquired infection and 4.7% (95% CI 3.9−5.5%) in participants with heterosexually acquired infection, and highest in perinatally infected participants aged 10–14 years when starting ART (27.7%; 95% CI 13.2−42.1%). Across all participants, significant predictors of TCVF were those with perinatal HIV aged 10–14 years, African origin, pre‐ART AIDS, NNRTI‐based initial regimens, higher pre‐ART viral load and lower pre‐ART CD4. Conclusions: The results suggest a beneficial effect of starting ART before adolescence, and starting young people on boosted PIs, to maximize treatment response during this transitional stage of development.